Penerapan Algoritma K-Mean Clustering Pada Kecelakaan Lalu Lintas Berdasarkan Kabupaten/Kota Di Provinsi Jawa Tengah Tahun 2020 - Valdi Irawan; Adhi Rizal; Intan Purnamasari (Jurnal Ilmiah Wahana Pendidikan, 2022)
The increase in population has resulted in the need for motorized vehicles so that it triggers traffic accidents. The grouping of traffic accident data is important to do, because it will make it easier for the police, especially the traffic accident unit in each district/city police station in Central Java province in reducing the number of traffic accidents. In this study, using Data Mining with the K-Means Algorithm with the aim of obtaining information about traffic accident data groups based on the incidence rate so that it is known the level of traffic accidents that occur in each district / city in the province of Central Java. By using the K-means algorithm, 3 clusters with different accident rates are obtained, cluster 1 is the low accident rate, cluster 2 is moderate, and cluster 3 is the highest accident rate